Akt/p27kip1 Pathway Is Not Involved in Human Insulinoma Tumorigenesis - Adriana Graciela Díaz; Andrea Paes de Lima; Paula Garibaldi; Maria de los Milagros Rubio; Florencia García; Marta Kral; Oscar D. Bruno (International Journal of Endocrinology)
Insulinomas are pancreatic neuroendocrine tumors (pNET), usually benign. Akt/p27kip1 is an intracellular pathway overexpressed in many pNET. There are no data regarding its expression in human insulinomas. We aimed to investigate the expression of Akt and p27kip1 in 24 human insulinomas and to compare them to their expression in normal surrounding islets. Staining was performed on embedded paraffin tissue using polyclonal antibodies against total Akt, p-Akt, p27kip1, and pp27kip1. p-Akt was the predominant form in insulinomas; they presented lower Akt and p-Akt expression than normal islets in 83.3% and 87.5% of tumors, respectively. p27kip1 and pp27kip1 were mainly cytoplasmic in both insulinomas and normal tissue. Cytoplasmic pp27kip1 staining was higher in insulinomas and surprisingly nearly half of the insulinomas also presented nuclear p27kip1 (p=0.029). No differences were observed in the subcellular localization of p27kip1 and activation of Akt between benign and malignant insulinomas. The low expression of Akt seen in insulinomas might explain the usual benign behavior of this type of pNET. Cytoplasmic p27kip1 in both insulinomas and normal islet cells could reflect the low rate of replication of beta cells, while nuclear p27kip1 would seem to indicate stabilization and nuclear anchoring of the cyclin D-Cdk4 complex. Our data seem to suggest that the Akt pathway is not involved in human insulinoma tumorigenesis.